Anke Finger and Julie Shoults, Editors. Women in German Expressionism: Gender / Sexuality / Activism. U of Michigan P, 2023. - Virginia L. Lewis (Studies in 20th & 21st Century Literature, 2026)
Review of Anke Finger and Julie Shoults, Editors. Women in German Expressionism: Gender / Sexuality / Activism. U of Michigan P, 2023. vii + 364 pp.
Keywords: German Expressionism; women; activism